Pengaruh Konsentrasi Abu Gosok dan Waktu Perendaman Air Terhadap Kandungan Nutrisi Tepung Buah Mangrove Avicenia marina - Permadi, Yusup Bayu; Sedjati, Sri; Supriyantini, Endang (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Nowadays, there are not much knowledge of mangrove fruit. One of mangrove species which has been used as source of food is A.marina. There are toxins such tannin and HCN in mangrove fruit. They may inhibit food process of mangrove fruit. So, they must be removed. The material for removing the toxins is ash powder. This study used factorial pattern of Randomized Complete with split plot Design with 2 treatments and 3 replication,i.e: water immersion time (1,2,3 day) and ash powder concentration (5,10,15% unity). Data was analyzed by two-way anova using SPSS. The result indicated that boiling treatment with ash powder and water immersion had a significant effect ( P<0,05) toward content of carbohydrate, lipid, protein of Avicennia marina fruit flour. Boiling treatment with 15 % ash powder and 3 days immersion had best result toward content of protein and lipid of Avicennia marina flour, while boiling treatment with 5% ash powder and 2 days immersion had best result toward content of carbohydrates of Avicennia marina flour.